Cooling flows around cold clouds in the circumgalactic medium: steady-state models and comparison with TNG50 - Dutta, Alankar; Sharma, Prateek; Nelson, Dylan (Monthly notices of the Royal Astronomical Society, 2022)
Cold, non-self-gravitating clumps occur in various astrophysical systems, ranging from the interstellar and circumgalactic medium (CGM), to active galactic nucleus outflows and solar coronal loops. Cold gas has diverse origins such as turbulent mixing or precipitation from hotter phases. We obtain the analytical solution for a steady pressure-driven 1D cooling flow around cold, local overdensities, irrespective of their origin. Our solutions describe the slow and steady radiative cooling-driven gas inflow in the saturated regime of non-linear thermal instability in clouds, sheets, and filaments. Such a cooling flow develops when the gas around small clumps undergoes radiative cooling. These small-scale, cold ‘seeds’ are embedded in a large volume-filling hot CGM maintained by feedback. We use a simple two-fluid treatment to include magnetic fields as an additional polytropic fluid. To test the limits of applicability of these analytical solutions, we compare with the gas structure found in and around small-scale cold clouds in the CGM of massive haloes in the TNG50 cosmological magnetohydrodynamic simulation from the IllustrisTNG suite. Despite qualitative resemblance of the gas structure, we find deviations from steady-state profiles generated by our model. Complex geometries and turbulence all add complexity beyond our analytical solutions. We derive an exact relation between the mass cooling rate ($\dot{\rm M}_{\rm cool}$) and the radiative cooling rate ($\dot{\rm E}_{\rm cool}$) for a steady cooling flow. A comparison with the TNG50 clouds shows that this cooling flow relation only applies in a narrow temperature range around $\rm \sim 10^{4.5}$ K where the isobaric cooling time is the shortest. In general, turbulence and mixing, instead of radiative cooling, may dominate the transition of gas between different temperature phases.